Crystal structure of 4-({(1E,2E)-3-[3-(4-fluorophenyl)- 1-isopropyl-1H-indol-2-yl]allylidene}amino)-1H- 1,2,4-triazole-5(4H)-thione - Kulkarni, Ajaykumar D.; Rahman, Md. Lutfor; Mohd. Yusoff, Mashitah; Huey, Chong Kwong; Ching, Kheng Quah (International Union of Crystallography, 2015)
The asymmetric unit of the titled compound, C22H20FN5S, comprises two independent molecules (A and B), both of which have a trans conformation with respect to the methene C C [1.342 (2) and 1.335 (2) A ° ] and the acyclic N C [1.283 (2) and 1.281 (2) A ° ] bonds. In molecule A, the triazole ring makes dihedral angles of 55.01 (12) and 18.17 (9) with the benzene and indole rings, respectively. The corresponding dihedral angles for molecule B are 54.54 (11) and 14.60 (10), respectively. In the crystal, molecules are consolidated into –A– B–A–B– chains along [010] via N—H N hydrogen bonds. The chains are further linked into layers parallel to the ac plane via – interactions involving inversion-related triazole rings [centroid–centroid distances = 3.3436 (11)– 3.4792 (13) A ° ].